High Performance Computing Environment using General Purpose Computations on Graphics Processing Unit - Andreas Widjaja; Tjatur Kandaga Gautama; Sendy Ferdian Sujadi; Steven Rumanto Harnandy (Maranatha University Press, 2021)
Here a report of a development phase of an environment of high performance computing (HPC) using general purpose computations on the graphics processing unit (GPGPU) is presented. The HPC environment accommodates computational tasks which demand massive parallelisms or multi-threaded computations. For this purpose, GPGPU is utilized because such tasks require many computing cores running in parallel. The development phase consists of several stages, followed by testing its capabilities and performance. For starters, the HPC environment will be served for computational projects of students and members of the Faculty of Information Technology, Universitas Kristen Maranatha. The goal of this paper is to show a design of a HPC which is capable of running complex and multi-threaded computations. The test results of the HPC show that the GPGPU numerical computations have superior performance than the CPU, with the same level of precision.